ON THE USE OF STATISTICAL METHODS TO INTERPRET ELECTRICAL RESISTIVITY DATA FROM THE EUMSUNG BASIN (CRETACEOUS), KOREA - Kim J.S.; Han S.H.; Ryang W.H. (My University, 2001)
Electrical resistivity mapping was conducted to delineate boundaries and architecture of the Eumsung Basin Cretaceous. Basin boundaries are effectively clarified in electrical dipole-dipole resistivity sections as high-resistivity contrast bands. High resistivities most likely originate from the basement of Jurassic granite and Precambrian gneiss, contrasting with the lower resistivities from infilled sedimentary rocks. The electrical properties of basin-margin boundaries are compatible with the results of vertical electrical soundings and very-low-frequency electromagnetic surveys. A statistical analysis of the resistivity sections is tested in terms of standard deviation and is found to be an effective scheme for the subsurface reconstruction of basin architecture as well as the surface demarcation of basin-margin faults and brittle fracture zones, characterized by much higher standard deviation. Pseudo three-dimensional architecture of the basin is delineated by integrating the composite resistivity structure information from two cross-basin E-W magnetotelluric lines and dipole-dipole resistivity lines. Based on statistical analysis, the maximum depth of the basin varies from about 1 km in the northern part to 3 km or more in the middle part. This strong variation supports the view that the basin experienced pull-apart opening with rapid subsidence of the central blocks and asymmetric cross-basinal extension.
Keywords: ELECTRICAL RESISTIVITY METHODS; STATISTICAL METHODS; FAULTS; EUMSUNG BASIN; KOREA; Cretaceous; Jurassic; Cambrian; Mesozoic::Cretaceous; Палеозой::Кембрийская; Mesozoic::Jurassic; Мезозой::Меловая; Мезозой::Юрская; Paleozoic::Cambrian